Parental perceptions of teen driving: Restrictions, worry and influence. (December 2016) - Jewett, Amy; Shults, Ruth A.; Bhat, Geeta
Abstract: Introduction: Parents play a critical role in preventing crashes among teens. Research of parental perceptions and concerns regarding teen driving safety is limited. We examined results from the 2013 Summer ConsumerStyles survey that queried parents about restrictions placed on their teen drivers, their perceived level of "worry" about their teen driver's safety, and influence of parental restrictions regarding their teen's driving. Methods: We produced frequency distributions for the number of restrictions imposed, parental "worry, " and influence of rules regarding their teen's driving, reported by teen's driving license status (learning to drive or obtained a driver's license). Response categories were dichotomized because of small cell sizes, and we ran separate log-linear regression models to explore whether imposing all four restrictions on teen drivers was associated with either worry intensity ("a lot" versus "somewhat, not very much or not at all") or perceived influence of parental rules ("a lot" versus "somewhat, not very much or not at all"). Results: Among the 456 parent respondents, 80% reported having restrictions for their teen driver regarding use of safety belts, drinking and driving, cell phones, and text messaging while driving. However, among the 188 parents of licensed teens, only 9% reported having a written parent-teen driving agreement, either currently or in the past. Worrying "a lot" was reported less frequently by parents of newly licensed teens (36%) compared with parents of learning teens (61%). Conclusions and Practical Applications: Parents report having rules and restrictions for their teen drivers, but only a small percentage formalize the rules and restrictions in a written parent-teen driving agreement. Parents worry less about their teen driver's safety during the newly licensed phase, when crash risk is high as compared to the learning phase. Further research is needed into how to effectively support parents in supervising and monitoring their teen driver.